2009
DOI: 10.1182/blood-2009-05-223958
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of CD137 immunomodulation in lymphoma and its enhancement by Treg depletion

Abstract: Despite the success of passive immunotherapy with monoclonal antibodies (mAbs), many lymphoma patients eventually relapse. Induction of an adaptive immune response may elicit active and longlasting antitumor immunity, thereby preventing or delaying recurrence. Immunomodulating mAbs directed against immune cell targets can be used to enhance the immune response to achieve efficient antitumor immunity. Anti-CD137 agonistic mAb has demonstrated antitumor efficacy in various tumor models and has now entered clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
117
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(120 citation statements)
references
References 36 publications
0
117
0
1
Order By: Relevance
“…Additional murine studies have demonstrated that co-administration of anti-GITR and anti-CTLA-4 mAbs have a synergistic effect, leading to eradication of tumors in a murine tumor model [11,13,50]. Mitsui Based on the results presented in this report, we have initiated a Phase I clinical trial in subjects with metastatic melanoma (ClinicalTrials.gov ID# NCT01216436).…”
Section: Discussionmentioning
confidence: 99%
“…Additional murine studies have demonstrated that co-administration of anti-GITR and anti-CTLA-4 mAbs have a synergistic effect, leading to eradication of tumors in a murine tumor model [11,13,50]. Mitsui Based on the results presented in this report, we have initiated a Phase I clinical trial in subjects with metastatic melanoma (ClinicalTrials.gov ID# NCT01216436).…”
Section: Discussionmentioning
confidence: 99%
“…Il a été montré -dans un modèle de souris immunocompétentes -qu'un anticorps agoniste anti-CD137 permet d'inhiber la croissance d'un lymphome in vivo et d'améliorer la survie des animaux, grâce au développement d'une immunité antitumorale s'inscrivant dans la durée. De plus, cet effet est renforcé par la déplétion des cellules Treg grâce à un anticorps dirigé contre le récepteur du folate-4 (FR4) [15]. Une autre stratégie actuellement explorée consiste à réévaluer l'effet thérapeutique de cytokines dont le déve-loppement a été arrêté du fait d'effets secondaires sévères aux doses utilisées, en les combinant avec des anticorps antagonistes.…”
Section: Les Anticorps Monoclonaux En Oncologie : Inhiber Les Inhibitunclassified
“…These clinical observations suggest that new treatment modalities to enhance host immunity (i.e., NK cells) might improve survival in cancer patients. One of those new treatments that it is currently undergoing clinical trials is anti CD 137 monoclonal antibody [53,54]. CD 137 is a surface glycoprotein that belongs to the tumor-necrosis factor receptor superfamily (TNFRSF) and is expressed by activated natural killer cells, T cells, and dendritic cells [53,54].…”
Section: Cut-off Values Of Absolute Lymphocyte Count and Absolute Lymmentioning
confidence: 99%
“…One of those new treatments that it is currently undergoing clinical trials is anti CD 137 monoclonal antibody [53,54]. CD 137 is a surface glycoprotein that belongs to the tumor-necrosis factor receptor superfamily (TNFRSF) and is expressed by activated natural killer cells, T cells, and dendritic cells [53,54]. In vivo studies have shown that anti CD137 enhances cytotoxicity of NK cells and induces a CD4+Th1 response [53].…”
Section: Cut-off Values Of Absolute Lymphocyte Count and Absolute Lymmentioning
confidence: 99%
See 1 more Smart Citation